Self-care Experiences of Older adults with Diabetes Mellitus Following Limb Amputation Living in Rural Areas - Yowapui, Panida; suriya, natthawut; Phimpha, Nutjariya; Deeprom, Keskanok (Princess of Naradhiwas University Journal, 2025)
This research article aimed to examine the self-care experiences of older adults with diabetes mellitus following limb amputation used a phenomenological qualitative research methodology. Key informants were twelve older adults with diabetes mellitus following lower limb amputation living in rural areas, Muang district, Maha Sarakham province. The period of data collection was February 2022–April 2022. Research instruments were an in-depth interview questionnaire, observations, field notes, and tape recordings. The Data were transcribed verbatim and analyzed by using thematic analysis. The findings revealed that three primary themes emerged from key informants’ definitions of self-care after limb amputation due to diabetes mellitus: 1) mental care, which included two subthemes: feeling of living with an incomplete organ and burdened by others; 2) physical part, which included two subthemes: losing one’s ability to work and changing one’s role in the family; and 3) stress coping strategies, which included three subthemes: self-consolation, limb amputation due to past karma, and dependence on others. Experiences of older adults with diabetes mellitus after limb amputation can serve as a basis information for preparing plans for their self-care after limb amputation to promote further appropriate treatment.